Portrait of Indonesian Vocabolary in Writing Skills: Case Study of Darul Maaref School Foundation, Thailand - Nasyahirah, Nurul; Febriyana, Mutia (JOLLT Journal of Languages and Language Teaching, 2024)
Indonesian is an asset for the Indonesian nation which is always maintained both in the realm of Education and non-Education. Therefore, Indonesian is expected to be global for other countries. Related to this, the Indonesian program for Foreign Speakers (BIPA) as a bridge in introducing the language to the world, namely through four language skills. One of them is writing skills. This study aims to determine students’ ability to write Indonesian vocabulary through theÂ Indonesian teaching program for foreign speakers (BIPA) at Darul Maaref School Foundation, Satun, Thailand. This research method is descriptive qualitative with a case study approach. The results of the study found that written language errors inÂ Darul Maaref School Foundation students included the use of incomplete sentence types, namely 11 data, word arrangement 3 data, capital letters 96Â data, pronouns 1Â data, prepositions 15Â data, word choice 27Â data, spelling 46Â data, hyphen 3Â data, and affix 2 data. The factors causing students’ written languageÂ errorsÂ areÂ caused byÂ the influence of spoken language, students have not fully understood Indonesian grammar, students have not carefullyÂ written Indonesian, and BIPA learning has not been effective.Â Related to these findings, BIPA teaching materials are needed by emphasizing Indonesian that are in accordance with the rules of Indonesian SpellingÂ (EBI)Â and presented as innovative and fun BIPA learning for students.